Afghanistan are we losing the peace? - Wisner, Frank (Frank G.); Platt, Nicholas; Boulton, Marshall M.; ebrary, Inc. (New York : Council on Foreign Relations, 2003)
Report on United States foreign policy following Operation Enduring Freedom in Afghanistan, with recommendations.
Executive summary -- Introduction -- The international effort in Afghanistan -- How to deal with growing insecurity -- Political developments -- External interference -- Reconstructing Afghanistan -- Afghans frustrated by slow economic progress -- Conclusions and recommendations.
Includes bibliographical references.
Electronic reproduction.
Keywords: Internal security -- Afghanistan; Humanitarian assistance -- Afghanistan; Afghanistan -- History -- 2001-; United States -- Military policy; United States -- Foreign relations -- 2001-2009.; Electronic books